EVALUASI KETERJANGKAUAN DAN KETERSEDIAAN SMA NEGERI BERDASARKAN SISTEM ZONASI PPDB PROVINSI JAWA TENGAH TAHUN 2023/2024 DI KOTA SEMARANG - Nigrum, Prisma Tia; Hayati, Rahma; Suharini, Erni; Indrayati, Ariyani (Jurnal Spasial, 2025)
The high mobility of high school students due to the uneven number of schools and equality in accessing education, initiated the government to form zoning regulations. The practice in the field shows that the zoning system has not been able to eliminate inequality in accessing education. This study aims to (1) analyze the distribution pattern of public high schools, (2) analyze the affordability of public high schools, (3) evaluate the availability of public high schools in Semarang City. Nearest neighborhood data analysis was used for distribution pattern, buffering with SNI 03-1733-2004 standard for affordability, Luthfi Muta'ali's availability formula for availability. The results of the study (1) the distribution pattern of public senior high schools in Semarang City shows a uniform/regular/dispersed pattern, 2) the affordability based on zoning regulations results in all sub-districts of Semarang City being affordable, but if using the SNI 03-1733-2004 standard there are 10 sub-districts and 30 villages that are not affordable or blankspots. (3) the availability of school facilities only three out of 16 sub-districts have a surplus level, around 20 additional schools are needed but still considering the number of private SMK/MA/SMA facilities in each sub-district.